Health information post-encountering behaviours on social media platforms - Khalid U Fallatah; Morgan A Harvey; Sophie Rutter (Information Research: An International Electronic Journal)
Introduction. While much research has been done into how people encounter information, little has investigated post-encountering behaviours and their motivating factors. This exploratory study aims to study people’s behaviours after encountering health information on social media platforms.